Selections from Eliza Leslie - Leslie, Eliza, 1787-1858.; Madden, Etta M., 1962- (Lincoln [Neb.] : University of Nebraska Press, 2011)
Best known for her culinary and domestic guides and the award-winning short story "Mrs. Washington Potts," Eliza Leslie deserves a much more prominent place in contemporary literary discussions of the nineteenth century. Her writing, known for its overtly moralistic and didactic tones-though often presented with wit and humor-also provides contemporary readers with a nuanced perspective for understanding the diversity among American women in Leslie's time.Leslie's writing serves as a commentary on gender ideals and consumerism; presents complicated constructions of racial, national, and class-
Fiction: The travelling tin-man; Mrs. Washington Potts; The settlers; Eliza Farnham, or The love letters; Mr. and Mrs. Woodbridge : a story of domestic life; Nothing morally wrong -- Nonfiction: Seventy-five receipts for pastry, cakes, and sweetmeats : an excerpt: Black cake, or Plum cake; Spunge cake; Almond cake; French almond cake; Maccaroons -- Domestic French Cookery : An excerpt; Preface; Miscellaneous receipts -- American girl's book, or Occupation for play hours : excerpts from Part III, "Amusing work : Pincushions; A strawberry; A basket pincushion; A bunch of hearts -- The Elephant -- The ladies' guide to true politeness and perfect manners, or Miss Leslie's behavior book : an excerpt -- Letters -- Conduct to literary women -- Notes -- Chronology of Eliza Leslie's published works.
Short stories and miscellaneous essays.
Includes bibliographical references.
English.
JSTOR
Keywords: Cooking, American; Handicraft; Etiquette for women; Cuisine américaine.; Artisanat; Savoir-vivre -- Femmes; crafts (art genres); Cooking, American; Etiquette for women; Handicraft